Redescription of Mycale tunicata (Schmidt, 1862) (Porifera, Demospongiae, Poecilosclerida) from Rovinj, Croatia, northern Adriatic Sea - Gugel, Jochen; Pfannkuchen, Martin; Brümmer, Franz (Zootaxa, 2006)
Entire specimens of the sponge Mycale (Aegogropila) tunicata (Schmidt, 1862) (Porifera, Demospongiae, Poecilosclerida) were obtained from a soft-bottom environment through dredging and SCUBA-diving from the bay of Rovinj. Reliable identification was only possible after thorough comparisons with Museum specimens, including the original material from O. Schmidt. For the first time photographs of various aspects (sponge in situ, freshly collected sponges, both ectosomal and choanosomal skeleton, the surface, all spicules) of the sponge can be presented. Since a lot of material exists and the available descriptions of the species are in parts incomplete or misleading (especially the original description by O. Schmidt) a redescription of the species with recently collected material is an urgent task. A lectotype from the Schmidt-syntypes is designated.